Breastfeeding Support Rooms and Their Contribution to Sustainable Development Goals: A Qualitative Study - De Souza, Carolina Belomo; Venancio, Sonia Isoyama; da Silva, Regina Paula Guimarães Vieira Cavalcante (Frontiers in Public Health, 2021)
Objectives: Breastfeeding support rooms are low-cost interventions that may prolong breastfeeding and improve work performance. We sought to understand the experiences and perceptions of working women who use breastfeeding support rooms and the potential contribution of these rooms to sustainable development goals. Methods: Descriptive and exploratory study was conducted through convenience sampling of women working in companies with breastfeeding support rooms in the state of Paraná, Brazil. A semi-structured questionnaire was applied through interviews and online self-completion. Results: 53 women between 28 and 41 years old participated in the study. 88.7% had graduated from college and 96% were married. From the experiences and perceptions of women, we identified that breastfeeding support rooms contribute to prolong breastfeeding, improve physical and emotional well-being, allow women to exercise their professional activities comfortably, contribute to the professional appreciation of women and to the good relationship between employees and employers. Conclusion: In this novel study, we demonstrate how, from the point of view of women, breastfeeding support rooms can contribute to 8 of the 17 Sustainable development goals and should therefore be encouraged and promoted.